TUIMP (The Universe In My Pocket) - Vale Asari, Natalia; Stasińska, Grażyna (Cadernos de Astronomia, 2024)
The TUIMP project (The Universe In My Pocket https://www.tuimp.org) is dedicated to the production of books on Astrophysics aimed at children, teenagers and those curious of any age. Available free of charge, these books can be printed on a single sheet of paper. They are prepared and reviewed by professionals in the field of astronomy and translated into fourteen languages by professional astronomers and astronomy students around the world, covering Portuguese, Afaan Oromo, Albanian, Arabic, Armenian, English, Spanish, French, Greek, isiZulu, Italian, Polish, Romanian and Russian.
Keywords: Astrophysics; education; outreach